Evaluation of nutritional quality of manures: Impact on yield and uptake of nutrients in fenugreek (Trigonella foenum-graecum) and soil properties under Typic Haplustepts - AISHWATH, O P; LAL, G; NAIMUDDIN, NAIMUDDIN; SINGH, BALRAJ (The Indian Journal of Agricultural Sciences, 2017)
A field study was carried out to assess the effect of different organic manures (Vermi-compost, sheep manure and farmyard manure) and Rhizobium inoculation on yield and uptake of nutrients in fenugreek (Trigonella foenumgraecum L.) and soil properties during 2011-12 and 2012-13. Result revealed that yield of fenugreek enhanced by the application of organic manures and seed inoculation with Rhizobium. However, yield obtained with farmyard manure was highest as compared to other inputs and control. The per cent yield increased with these manures and Rhizobium was 11.45, 20.83, 22.22 and 35.42 with Rhizobium, sheep manure, vermi-compost and FYM, respectively. Chlorophyll content and uptake of macro and micronutrients in fenugreek and soil available macronutrients were more with FYM. Total chlorophyll content was more at 90 days followed by 30 and 60 days. Uptake pattern of nutrient indicated that N, K, Fe, Mn and Cu accumulation was more in straw than seed. Contrary to it, P and Zn accumulation was more in seed than straw. Straw yield and availability of micronutrients except Mn did not influence either by manures or seed inoculation with Rhizobium. Soil organic carbon was only higher with sheep manure and FYM. Regardless, it has been cited in some of the literature that vermi-compost is always better than any other farm manures, however our results are warranted. The nutritional value of FYM was the best and vermi-compost was found poorest among the commercially available manures used in this study.